Formation of p-type CdS thin films by laser-stimulated copper diffusion - Dzhafarov, TD; Altunbas, M; Kopya, AI; Novruzov, V; Bacaksiz, E (IOP PUBLISHING LTD, 1999)
A new fabrication technique of p-type CdS thin films by He-Ne laser illumination of bilayer Cu-nCdS structures at room temperature was investigated. The n-type CdS films were obtained by vacuum evaporation in a quasi-closed volume. X-ray diffraction was used to provide crystalline structure and composition data of CdS films and Cu-CdS structures. The band gap of CdS films was estimated from the optical transmission spectra. The hot probe and Hall effect studies were used for the determination of conductivity type and concentration of charge carriers in films. The formation of a p-n homojunction in CdS films or conversion of the film all over to the p-type, depending on the duration of laser illumination, was shown by I-V characteristics, the photovoltaic, the hot probe and Hall effect measurements. Analysis of concentration distributions of Cu in CdS films, arising as a result of laser-accelerated diffusion, by energy dispersive x-ray spectroscopy gave the effective diffusion coefficient of copper, D = 8 x 10(-12) cm(2) s(-1) at T = 25 degrees C.
Keywords: CELLS; Physics